Detection of GM1‐gangliosidosis in newborn dried blood spots by enzyme activity and biomarker assays using tandem mass spectrometry. Issue 1 (26th August 2020) - Su, Peiling; Khaledi, Hamid; Waggoner, Christine; Gelb, Michael H.
Abstract: GM1‐gangliosidosis is a rare autosomal recessive lysosomal storage disease caused by deficiency of β‐galactosidase (GLB1). Newborn screening (NBS) may be warranted in the near future given the initiation of a number of gene therapy clinical trials. Here, we report a tandem mass spectrometry (MS/MS) enzymatic assay of GLB1 using dried blood spots (DBS), and the demonstration that GLB1 activities in newborn DBS from seven GM1‐gangliosidosis patients are well below those measured in random newborn DBS. MS/MS analysis of two glycan biomarkers, dp5 and A2G2, shows high elevation in newborn DBS from GM1‐gangliosidosis compared to the levels in the nonaffected reference range. Abstract :